Optimal inflation-growth threshold: A case of the ECOWAS members states - Olorunsola E. Olowofeso; Ebrima N. Wadda; Adegoke I. Adeleke; Joseph R. Yengbe; Yaya Cham; Tapia M. Kanu (West African Monetary Institute (WAMI), 2024)
This study provides country-specific empirical evidence on the optimal inflation-growth threshold in the ECOWAS (WAEMU and WAMZ) region from 1996-2022. Although there is large empirical literature on this subject, however, previous studies generally focused on exogenous approaches of determining optimal inflation which impose a sharp and most often linear behaviour on the threshold level of inflation. This paper contributes to the policy debate on the inflation-growth nexus by endogenously determining the individual country inflation threshold for fourteen (14) ECOWAS countries. The results from the study indicate that most of the countries have inflation in the lower regime to be positive while the high inflation regime is strongly negative, suggesting adverse effects of high inflation on growth. This finding is consistent with the theoretical proposition. It also shows varied threshold inflation across the region of ECOWAS, with optimal inflation rates for WAEMU - Benin (1.33%), Burkina Faso (2.00%), Cote-D'Ivoire (3.64%), Guinea-Bissau (3.68%), Mali (3.49%), Niger (3.17%), Senegal (1.66%) and Togo (3.89%), having inflation-growth threshold hovering around 1 to 4 percent. This is quite different to that of the WAMZ countries where The Gambia (4.93%), Ghana (10.44%), Guinea (9.21%), Liberia (8.72%), Nigeria (10.50%) and Sierra Leone (6.96%), are having a relatively higher inflation threshold, hovering around 5 to 11 percent. These findings suggest a potential difference in inflation tolerance levels in the ECOWAS (WAEMU and WAMZ) region. It is remarkable to note that the current ECOWAS Convergence criteria where the same level of lower single digit of inflation (5 percent) is being applied across all ECOWAS regions may not be growth enhancing for all the member states, particularly the WAMZ, where there appear to be more inflationary tolerance level and capacity to absolve relatively higher level of inflation. Therefore, there may be need to revisit this issue and consider a possibility of having a "range" inflation convergence criterion rather than "point. Lastly, Central Banks are encouraged to continue to pursue appropriate monetary policy measures to lower inflation to the desirable single-digit level.
Keywords: E31; O47; C22; 330; Inflation; Growth; Threshold Effects; Smooth Transition Regression; ECOWAS